Co‐occurrence and hybridization of anther‐smut pathogens specialized on Dianthus hosts. Issue 7 (22nd March 2017) - Petit, Elsa; Silver, Casey; Cornille, Amandine; Gladieux, Pierre; Rosenthal, Lisa; Bruns, Emily; Yee, Sarah; Antonovics, Janis; Giraud, Tatiana; Hood, Michael E.
Abstract: Host specialization has important consequences for the diversification and ecological interactions of obligate pathogens. The anther‐smut disease of natural plant populations, caused by Microbotryum fungi, has been characterized by specialized host–pathogen interactions, which contribute in part to the isolation among these numerous fungal species. This study investigated the molecular variation of Microbotryum pathogens within the geographic and host‐specific distributions on wild Dianthus species in southern European Alps. In contrast to prior studies on this pathogen genus, a range of overlapping host specificities was observed for four delineated Microbotryum lineages on Dianthus hosts, and their frequent co‐occurrence within single‐host populations was quantified at local and regional scales. In addition to potential consequences for direct pathogen competition, the sympatry of Microbotryum lineages led to hybridization between them in many populations, and these admixed genotypes suffered significant meiotic sterility. Therefore, this investigation of the anther‐smut fungi reveals how variation in the degrees of host specificity can have major implications for ecological interactions and genetic integrity of differentiated pathogen lineages.